Measurement of radon concentration and exhalation rate in some mud houses of district Lahore, Pakistan. Issue 6 (October 2014) - Mahmood, Arif; Tufail, M.; Iqbal, M. Azhar
Some low-income people of Pakistan live in traditional windowless one- to two-room houses made of mud. The data on radon concentration in such houses of Pakistan was scarce in the literature. Therefore, 60 mud houses in the vicinity of the city of Lahore (the capital of the Punjab province of Pakistan) were selected for survey of radon in these houses. The passive integrating technique with CN-85 track detectors was employed for the measurement of radon. Indoor and outdoor radon concentrations were determined to be 114.88 ± 66.79 (18.37 − 269.58) and 10.78 ± 2.70 (8.08 − 13.57) Bq m −3, respectively. Radon concentration was higher in the mud-made houses than that in the dwellings constructed of bricks and Portland cement. Radon exhalation rate from the walls and floors of the mud houses was measured to find the correlation with indoor radon concentration. A weak positive correlation was observed between these two quantities. From the measured concentration of radon, annual effective dose and excess lifetime cancer risk were derived to be 2.54 ± 1.47 (0.41 − 5.95) mSv and (15.34 ± 8.92) × 10 −3 (1.53 ± 0.89 %), respectively. Relatively higher radon concentration in the mud houses was due to the little exchange of air in these houses. Ventilation is recommended for the mitigation of radon from these houses.